2-Deoxyglucose alleviates migraine-related behaviors by modulating microglial inflammatory factors in experimental model of migraine - Qiu, Tao; Zhou, Yanjie; Hu, Luyu; Shan, Zhengming; Zhang, Yu; Fang, Yuting; Huang, Wanbin; Zhang, Lily; Fan, Shanghua; Xiao, Zheman (Frontiers in Neurology, 2023)
Background Targeting metabolic pathways has emerged as a new migraine treatment strategy as researchers realize the critical role metabolism plays in migraine. Activated inflammatory cells undergo metabolic reprogramming and rely on glycolysis to function. The objective of this study was to investigate the glycolysis changes in the experimental model of migraine and the effect of glycolysis inhibitor 2-Deoxy-D-glucose (2-DG) in the pathophysiology of migraine. Methods We used a rat model of migraine that triggered migraine attacks by applying inflammatory soup (IS) to the dura and examined changes in glycolysis. 2-DG was used to inhibit glycolysis, and the effects of 2-DG on mechanical ectopic pain, microglial cell activation, calcitonin gene-related peptides (CGRP), c-Fos, and inflammatory factors induced by inflammatory soup were observed. LPS stimulated BV2 cells to establish a model in vitro to observe the effects of 2-DG on brain-derived neurotrophic factor (BDNF) after microglia activation. Results In the experimental model of migraine, key enzymes involved in glycolysis such as phosphofructokinase platelet (PFKP), hexokinase (HK2), hypoxia inducible factor-1α (HIF-1α), lactate dehydrogenase (LDH) and pyruvate kinase (PKM2) were expressed in the medullary dorsal horn. While the expression of electronic respiratory transport chain complex IV (COXIV) decreased. There were no significant changes in glucose 6-phosphate dehydrogenase (G6PD), a key enzyme in the pentose phosphate pathway. The glycolysis inhibitor 2-DG alleviated migraine-like symptoms in an experimental model of migraine, reduced the release of proinflammatory cytokines caused by microglia activation, and decreased the expression of CGRP and c-Fos. Further experiments in vitro demonstrated that glycolysis inhibition can reduce the release of Iba-1/proBDNF/BDNF and inhibit the activation of microglia. Conclusion The migraine rat model showed enhanced glycolysis. This study suggests that glycolytic inhibitor 2-DG is an effective strategy for alleviating migraine-like symptoms. Glycolysis inhibition may be a new target for migraine treatment.